Мінімізація дозового навантаження в алгоритмах рентгенівської комп’ютерної томографії - Bulavin, L. A.; Zabashta, Yu. F.; Motolyha, O. V. (Publishing house "Academperiodika", 2019)
An algorithm has been developed for the reconstruction of an X-ray image obtained at the minimum dose load on the researched object and provided a given image accuracy. This algorithm combines approaches typical of the inverse projection and regularization methods. The image is formed by overlaying filtered projections, and the filtering parameters are determined from the minimum condition for the difference between the discrepancy and the experimental error.